Teaching assimilations to improve listening skills for Vietnamese students (Journal of Contemporary Educational Policies and Practices, 2020)
Few would deny that at the very first stage of learning, language learners have to spend most of their time on practising listening skills in communication inside and outside class. They have to listen to others speaking, listen to themselves while talking and even implicitly while reading and writing. Listening is an important way of acquiring the language as well as picking up the structures and vocabulary. With a careful observation of the current situation of Vietnamese learners’ listening competencies and a thorough review of reference materials in English language teaching and learning, it is hoped that the study will help heighten students’ awareness of the problematic sounds that they encounter when listening to colloquial, casual and connected speech.
Keywords: Assimilation; connected speech sounds; listening skills